2022
DOI: 10.1039/d1bm01821c
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh SERS activity of the TiO2@Ag nanostructure leveraged for accurately detecting CTCs in peripheral blood

Abstract: Circulating tumor cells (CTCs) usually shed from primary and metastatic tumors serve as an important tumor marker, and easily cause fatal distant metastasis in cancer patients. Accurately and effectively detecting...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 55 publications
(63 reference statements)
0
17
0
Order By: Relevance
“…In the UV-Vis spectrum of nanostructures ( Figure 3 A), different absorption bands can be observed by changing the introduction of different materials. The absorption peak around 300–400 nm is related to the absorption of TiO 2 -Ag band gap, while the change of absorption peak produced at 400–800 nm can be related to Ag-induced surface plasmon resonance (SPR) [ 34 , 42 , 43 ]. It can be observed that the absorption peak will blue shift with the change of the structure ( Figure 3 A), This may be because the Ag and TiO 2 binding in the nanostructure reconstructs the Fermi level as the structure changes [ 44 , 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the UV-Vis spectrum of nanostructures ( Figure 3 A), different absorption bands can be observed by changing the introduction of different materials. The absorption peak around 300–400 nm is related to the absorption of TiO 2 -Ag band gap, while the change of absorption peak produced at 400–800 nm can be related to Ag-induced surface plasmon resonance (SPR) [ 34 , 42 , 43 ]. It can be observed that the absorption peak will blue shift with the change of the structure ( Figure 3 A), This may be because the Ag and TiO 2 binding in the nanostructure reconstructs the Fermi level as the structure changes [ 44 , 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Precious metals with local surface plasmon resonance (LSPR) properties are usually deposited on the template to enhance the local electromagnetic field, while other materials, such as nano-porous GaN [ 27 , 28 ], Si [ 29 , 30 ] and ZnO [ 30 ], are also used in this process because of their corresponding properties. TiO 2 is often used as an excellent carrier material because of its special optical [ 31 , 32 ] and chemical properties, so it is one of several widely used wide band gap semiconductors [ 33 , 34 ]. In this paper, a simple and efficient method for the preparation of nanostructure arrays is proposed by using the complementary method of plasma etching and magnetron sputtering and three kinds of nanocomposite structures with different hot spots are prepared.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, SERS technology serving as a bio probe has been increasingly applied to detect circulating tumor cells due to its unique detection advantages. [234][235][236][237][238][239][240][241][242][243][244] In the past few years, the detection of CTCs using SERS has been extensively studied. Wu and co-authors developed an AuNP-MBA-rBSA-FA SERS bioprobe for the direct detection of CTCs in blood with high specificity and high sensitivity.…”
Section: Ml-enabled Detection Of Circulating Tumor Cellsmentioning
confidence: 99%
“…60,61 A good example of such a synergetic combination is a TiO 2 @Ag nanostructure, developed by Xu et al for the ultrasensitive detection of CTCs. 217 The authors prepared a TiO 2 @Ag nanostructure by modifying Ag on the surface of TiO 2 NPs. The particles are further functionalised with R6G molecules (SERS tag), reduced bovine serum albumin (rBSA, increase stability and reduce non-specificity binding) and folic acid (FA, target molecule to specifically recognize cancer cells) (Fig.…”
Section: Sers Analysis Of Biomarkers On Cells and Evsmentioning
confidence: 99%